A rapid microwave-assisted method of synthesizing wurtzite Cu2ZnSnS4 in a novel solvent and its controlled phase evolution. Issue 21 (1st November 2022) - Dong, M.R.; Chai, X.H.; Qing, H.M.; Shen, T.; Cui, J.; Liu, J.K.; Zhu, Y.
Abstract: Stable pure wurtzite Cu2 ZnSnS4 (CZTS) microparticles are successfully synthesized and the phase control evolution is studied, where a mixture of ethylene glycol (EG) and triethylenetetramine (TETA) is used in conjunction with a rapid and low-cost microwave-assisted method to control the crystalline phases of the particles. The CZTS phase is mainly controlled by changing the reaction time, reaction power, surfactant vs. raw material ratio. The particles are characterized with X-ray diffraction, Raman spectroscopy, scanning electron microscope, transmission electron microscope and UV–vis spectrophotometer. The results show that when EG and TETA are mixed in a ratio of 1:6 and the reaction power is 800 W, CZTS in pure wurtzite phase is obtained rapidly when the raw material ratio is Cu: Zn: Sn: S = 2 : 1.25: 1: 6 and the reaction time is 120 s. The phase transition can be effectively controlled by controlling the reaction conditions such as raw material ratio, reaction power and reaction time.